Counterfeiting of milk and dairy products, and analytical methods suitable for the detection of counterfeiting - Csapó János; Albert Csilla; Szigeti Tamás János (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2020)
In the first part of this review article, the authors write about food counterfeiting in general, and then seek answers to the following questions: Are foods counterfeited today? What does food counterfeiting means and how to combat it? What official measures should be taken when food counterfeiting is detected? What sanctions can be imposed in case of food counterfeiting? In the context of counterfeiting milk and dairy products, the authors of the article report on the counterfeiting of milk from various animal breeds, such as buffalo, goat’s and sheep’s milk, as well as breast milk using cow’s milk, and also on mixing soy milk to cow’s milk. They also describe the detection of whey and buttermilk in milk, the determination of whey protein in dairy products, the analysis of milk produced from milk powder and other possibilities of milk and dairy product counterfeiting. Finally, they report on the detection of other fats in milk, butter and ghee (a traditional Indian butter formula made from buffalo milk – the Editor), the watering of milk, the determination of the extent of heat treatment of milk and dairy products, and the detection of the amount of spoiled milk unfit for consumption. The manuscript also describes the principles of analytical methods suitable for the detection of counterfeiting.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék